Metabolic activities of eight oil palm progenies grown under aluminum toxicity - Eka Tarwaca Susila Putra; Benito Heru Purwanto; Cahyo Wulandari; Taufan Alam (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Putra ETS, Purwanto BH, Wulandari C, Alam T. 2021. Metabolic activities of eight oil palm progenies grown under aluminum toxicity. Biodiversitas 22: 3146-3155. In Indonesia, oil palm is mostly cultivated on red-yellow podzolic soils, which mainly contain the high availability of aluminum (Al). This condition might affect oil palm growth i.e stunted growth and root damage. Therefore, this study was aimed to characterize metabolic activities and growth of eight oil palm progenies under Al toxicity. The study was conducted from January to December 2018 in Bendosari Hamlet, Madurejo Village, Prambanan Sub-District, Sleman District, Province of Yogyakarta, Indonesia. The trial was laid out in a randomized complete block design (RCBD) factorial with three blocks as replications, with experimental factors including oil palm progenies and Al concentration. The observation was conducted on Al concentration in the planting medium, metabolic activities, and oil palm growth. The data were analyzed using ANOVA, PLS-SEM, stepwise regression, hierarchical clustering heatmap, and GGE-Biplot. The results showed that Simalungun, Dumpy, and Yangambi progeny could grow and adapt better than other progenies in Al toxicity conditions. The resistance to Al poisoning mechanism was shown by a relatively low activity of O2-, H2O2, MDA, and REL, whereas SOD, POD, GB, AARed, ?-Toch, TPC RDW and, SDW showed higher relatively.